Community Health Centres: An Innovative Approach to Newcomer Settlement Services - Janet McLellan (Refuge, 1997)
While NGO settlement agencies face increasing challenges to deliver bath ethnospecific and larger broad-based programs for immigrants and refugees, Community Health Centres (CHCs) in large urban areas of Ontario have developed innovative means to meet the health and settlement needs of newcomers. Positive mental and physical health through access to medical and social resources, recognition of health determinants and enhanced participation in decision making are integral elements of CHC settlement and integration programs and services, all within the context of medical care. Through extensive outreach programs to newcomer communities, CHCs enhance the efectiveness of ethnospecific groups to define culturally appropriate services. CHCs provide an example of desired social change through a mainstream institutional basis.